The biochar: an alternative energy for the development of the sahel countries (case study of Senegal and Mali) - Banda Fall, Abibatou (Ciência & Trópico, 2013)
ABSTRACT For thirty years, the international energy situation has been characterized by a growing demand for domestic energy. The steady increase in world population has led to increased deforestation, strengthening then, climate change and pushing applicants to use the maximalist practices of natural resource use. Scenarios of the International Energy Agency showed that the actual energy demand will grow from 1,6% to 2% per year, and therefore it will increase by 50%, in 2030 (JLFELLOUS; GAUTIER, 2007). This crisis is not an exception in the Sahel region, which has considerable potential for biomass energy. Wood and coal, 89% of energy used in the Sahel, are currently available, but their energy is far from clean. So, to maintain a healthy environment, it is urgent to develop and popularize alternative energy sources such as bio-char, launched in Senegal and Mali since the 90’s. Its development is a great interest in the framework of diversification strategies and energy supply in the Sahel. Its popularization would, moreover, reduce environmental costs, as well as the economic and social impacts of these environmental problems that limit the development capacity of the Sahel. KEYWORDS: Biochar. Alternative energy. Development of the Sahel. RESUMO Por 30 anos, a situação energética internacional tem sido caracterizada por uma procura crescente de energia doméstica. O aumento constante da população mundial tem levado ao aumento do desmatamento, fortalecendo, em seguida, as alterações climáticas e empurrando os candidatos a usarem as práticas maximalistas de uso dos recursos naturais. Cenários da Agência Internacional de Energia mostraram que a demanda real de energia vai crescer de 1,6% a 2% ao ano e, portanto, aumentará em 50% em 2030 (JLFELLOUS; GAUTIER, 2007). Essa crise não é uma exceção na região do Sahel, que tem considerável potencial para energia de biomassa. A madeira e o carvão, 89% da energia utilizada no Sahel, estão atualmente disponíveis, mas sua energia está longe de ser limpa. Assim, para manter um ambiente saudável, é urgente desenvolver e popularizar fontes alternativas de energia, tais como bio-carvão, lançado em Senegal e Mali desde os anos 1990. Seu desenvolvimento é um grande interesse no quadro das estratégias de diversificação e fornecimento de energia na região do Sahel. Sua popularização poderia, além disso, reduzir os custos ambientais, bem como os impactos econômicos e sociais desses problemas ambientais que limitam a capacidade de desenvolvimento do Sahel. PALAVRAS-CHAVE: Biocarvão. Energia alternativa. Desenvolvimento do Sahel.